The Historical Background of The Ideology of Terrorism In Indonesia After September 11, 2001 - Muhammad Nasir (AJIS: Academic Journal of Islamic Studies, 2016)
The terrorist attact on September 11, 2001, became a turning point as well as a feedback in stipulating the emergence of other radical movements in many parts of the world. This on-going phenomenon can be regarded as global terrorist. Terrorism does not suddenly exist in Indonesia. There is a long history behind its existence. Tracing the history of the ideology is very important to minimize or avoid a bias judgment. Moreover, the term terrorism is usually used by certain groups to discredit particular religion even used as a commodity by advance country to judge the development country in order to create global secure. Keyword: terorism, fundamentalism, radicalism